Can Machines Discriminate? - Mendoza Munar, Lainiver; Urbano, Maria Karolina (Law, State and Telecommunications Review, 2024)
[Proposal] To take a first step towards the demand for responsible technological development, since like any tool created by the human being, it can be used for the benefit of humanity or against it. [Methodology/Approach/Design] In the initial stage of the research project titled "Discrimination and Ethics of Artificial Intelligence," a comprehensive review of literature and documents in the field of philosophy of mind and cognitive science during the latter half of the 20th century was conducted. This review aimed to establish connections with contemporary advancements in the ethics of artificial intelligence, particularly following the establishment of ethical principles by the European Community in 2019. The disciplines of philosophy of mind and cognitive science, being closely linked to neurobiology and artificial intelligence, were pioneers in recognizing the challenges associated with the development of this technology. However, at that time, artificial intelligence applications had not permeated all aspects of human activities as extensively as they do today. Consequently, the problems surrounding this technology were more speculative rather than urgent concerns. The rapid integration of artificial intelligence into various domains has presented society, governments, and companies with pressing issues that demand immediate attention. Given the recent nature of these advancements, adequate preparedness to address the associated challenges remains lacking. While ethics may lie outside the realm of scientific inquiry as it does not fall within its scope or methods, science plays a crucial role in the subject matter of ethics, as the tools created by humans can be employed for both harm and societal well-being. Once these tools begin to generate adverse consequences for individuals and society, ethical and legal considerations become paramount. The resurgence of interest in the philosophy of mind stems from the realization that ethical dilemmas associated with artificial intelligence are rooted in long-standing ethical problems. We continue to seek improved responses to such dilemmas and grapple with questions that arise from indeterminate concepts like equality. It is important to recognize that discrimination, by definition, goes against the principle of equality, and there are instances where machines contribute to discriminatory actions or situations. It is worth noting that addressing the questions posed in this article, within the context of a research project focused on discrimination, necessitates an interdisciplinary analysis. This further justifies the reliance on the disciplines of philosophy of mind and cognitive science, which approach the challenges of artificial intelligence from scientific, technological, linguistic, and philosophical perspectives, extending their reach into the legal domain as well. [Purpose] This article aims to emphasize the significance of conducting responsible technological advancements, particularly in the realm of artificial intelligence. It underscores the necessity for AI-based technologies to be designed with careful consideration of ethical and moral principles, ensuring that their impact aligns with societal norms and upholds the recognition of human rights. [Practical Implications] As Artificial Intelligence continues to permeate numerous facets of society, it is crucial to acknowledge the inherent risks associated with its usage, particularly in relation to discrimination. Consequently, it becomes imperative to implement measures that effectively mitigate these risks and reduce the potential for discriminatory outcomes.